An ultralight silica-modified ZrO2–SiO2 aerogel composite with ultra-low thermal conductivity and enhanced mechanical strength. (15th January 2018) - Hou, Xianbo; Zhang, Rubing; Fang, Daining
Abstract: A novel, ultralight, ZrO2 -fiber-reinforced ZrO2 –SiO2 aerogel composite with superior thermal and mechanical properties is fabricated via a rapid gelation method. Pure ZrO2 -SiO2 aerogel is modified by silica to effectively strengthen its nanostructure. The results demonstrate that the fabricated fiber-reinforced aerogel composites with ZrO2 -fiber contents ranging from 0 to 15 wt% exhibit ultra-low densities (0.16–0.33 g/cm 3 ), low thermal conductivities (0.0235–0.0296 Wm − 1  K − 1 ), and high compressive strengths (0.36–0.82 MPa). The present study provides an efficient method to prepare light aerogel composites with low thermal conductivity and high mechanical strength, which can be used as superior heat-insulators in aerospace applications. Graphical abstract: Image 1